Fatores associados ao conhecimento sobre as informações do Termo de Consentimento Livre e Esclarecido de participantes de um ensaio clínico realizado no Nordeste de Minas Gerais/Brasil - Lucas Henrique Lobato de Araujo (2012)
The study aimed to analyze, in a clinical trial, the association between participant´s knowledge relating to information contained in an Informed Consent Form (ICF) and socioeconomic/demographic factors, knowledge regarding medical and methodological terms, auto evaluation of health status, previous experience in clinical research and previousparticipation in educational interventions. Participated in the study 148 individuals, who consented to join in a clinical trial study held in the Americaninhas district, Minas Gerais, which endeavored to test a functional food with anti-helminthic properties. This is a descriptive study with a quantitative approach and cross-section design. A structured form,approaching themes contained in the Clinical Trial ICF, was used as a data collection method. The structure form application occurred in October 2011, one month after the participants signed the Clinical Trial ICF. The mean global knowledge of participants, regardinginformation contained in the ICF, was 57,26%. A multivariate analysis showed that a higher weekly access to electronic media, formal education, previous participation in educational interventions and previous knowledge regarding medical and methodological terms werepositively associated with global knowledge; while age was negatively associated with it.. Questions related to exams and procedures of clinical trial presented high percentage of accuracy (92,59%), while knowledge about clinical trial sponsor and duration presented low accuracy (18,24%). The knowledge regarding the purpose of the trial (47,30%), the reason for the invitation to participate in this study (32,43%), adverse events (44,59%) and research intended benefits (73,21%) presented moderate percentage of accuracy. The analysis of participant´s rights showed high percentage of correctness in knowledge concerning: theabsence of financial incentive to join in the clinical investigation (89,02%), the medical assistance alternatives granted due to participation on the clinical trial (77,20%) and the right to withdraw from the study (90,05%). Knowledge on the topic of participants data confidentiality (70,94%) and continuity of treatment in case of withdrawal (31,81%) wereconsidered moderated. The analysis on the subject of technical and methodological health terms revealed that knowledge of the terms placebo and randomization was low (2,02% and 8,78% respectively), while knowledge of the term adverse effects was moderated (41,89%)and knowledge concerning the terms medication and exams were high (83,78% and 87,16%, respectively). In conclusion, formal education and frequent access to electronic media are positively associated with knowledge of ICF information, while age is negatively associated.